ACE inhibitory tetrapeptides from Amaranthus hypochondriacus 11S globulin - Vecchi, Bruno (2009)
Amaranth seed is a valuable source of dietary protein with very high nutritional quality, and recently its potential as a nutraceutical has been proposed. The aim of this work was to provide experimental evidence for the presence of anti-hypertensive peptides in globulin 11S, one of the major constituents of the seed, by means of an in-silico based peptide library screening method. A three-dimensional model of globulin 11S was built, upon which anti-hypertensive peptides were mapped via a database-driven method. Solvent accessibility was evaluated for each potential peptide, and two potent and exposed tripeptides were detected: IKP and LEP. An N-terminal extension of these two peptides was built using the globulin 11S primary sequence information, and ACE inhibitory behaviour was simulated by automated ligand-protein docking. The occurrence of two inhibitory tetrapeptides, ALEP and VIKP, was predicted and experimentally validated by an in vitro ACE inhibition assay that showed IC50 values of 6.32 mM and 175 μM, respectively. This study is the first to provide experimental proof of the anti-hypertensive value of Amaranth. Furthermore, this is the first time that a peptide docking approach is used to find ACE-inhibitory peptides from a food protein source.